2021
DOI: 10.1007/s11250-021-02861-6
|View full text |Cite
|
Sign up to set email alerts
|

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics

Abstract: The present study assessed the influence of the type of the tropical pastures on lamb body weight (BW) gain and meat quality. Fifty-four lambs were allocated to three grazing pastures: (1) AG -Aruana grass (Panicum maximum cv. IZ-5); (2) PPpigeon pea legume (Cajanus cajan cv. Anão); and (3) CS -contiguous swards, half of the paddock with AG and half with PP. After 92 days of grazing, the lambs were slaughtered. Carcasses were evaluated and the longissimus muscle was collected to determine color, lipid profile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Additionally, the CP content of Cajanus cajan (L.) Millsp. sampled during both dry and rainy seasons ( Table 2 ) were in line with those reported by Miano et al [ 40 ], Hampel et al [ 41 ] and Valadares Filho et al [ 42 ] (17 to 24% CP), resulting in an average CP content of the MIX treatment being 25–45% greater than that of the REC and DEG during the experimental period, which may have contributed to the better animal performance of this treatment. In forage diets, the NDF content is one of the determinants of forage intake [ 43 ], and the DEG and REC treatments showed NDF and ADF values in line with those reported for Urochloa spp.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Additionally, the CP content of Cajanus cajan (L.) Millsp. sampled during both dry and rainy seasons ( Table 2 ) were in line with those reported by Miano et al [ 40 ], Hampel et al [ 41 ] and Valadares Filho et al [ 42 ] (17 to 24% CP), resulting in an average CP content of the MIX treatment being 25–45% greater than that of the REC and DEG during the experimental period, which may have contributed to the better animal performance of this treatment. In forage diets, the NDF content is one of the determinants of forage intake [ 43 ], and the DEG and REC treatments showed NDF and ADF values in line with those reported for Urochloa spp.…”
Section: Discussionsupporting
confidence: 89%
“…In both seasons, the CT content of the DEG and REC treatments were higher than the content of other tropical grasses reported by Bueno et al [ 51 ], while the MIX treatment presented values higher than those found by Pereira et al [ 47 ] for pigeon pea, and values lower than those found in a tropical pasture intercropped with pigeon pea [ 41 ]. Some studies have shown that feed consumption by ruminants can be reduced when the concentration of TC exceeds 50 g CT/kg DM, due to the reduction in acceptability and conditioned aversion [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations